The role of ANLN in malignant tumors: pathogenesis, treatment resistance and targeted strategies - Wang, YiXuan; Xiao, Yang; Yu, JieLin; Zou, YuanHua; Wang, Zhe; Yang, XiangHong (Frontiers in Cell and Developmental Biology, 2026)
ANLN is a highly conserved actin-binding protein that plays a critical role in cytokinesis by interacting with key cytoskeletal components such as actin, myosin, and RhoA. Increasing evidence shows that ANLN is aberrantly overexpressed in various cancers, including lung, breast, and liver cancers, and that its elevated expression is associated with enhanced tumor cell proliferation, migration, and invasion. Because of its central involvement in tumorigenesis and disease progression, ANLN has emerged as a promising prognostic biomarker and potential therapeutic target. Recent studies have demonstrated that ANLN contributes to resistance to chemotherapy, targeted therapy, and immunotherapy through multiple molecular mechanisms. This review provides a systematic overview of the physiological functions of ANLN, its roles in cancer initiation and progression, and its regulatory mechanisms in treatment resistance, offering biological insights into precision oncology and potential strategies for overcoming therapeutic resistance in cancer.